Perbandingan Pendapatan Petani dengan Pendapatan Pengemis di Kota Denpasar - SIMBOLON, TORKIS JOEL; WINDIA, I WAYAN; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.2, April 2016)
Abstract Comparison Between Farmers and Beggar in Denpasar According to the Earnings Agricultural sector have a very important role in national economical. This situation can be identified by a dominant contribution, either directly or indirectly in the goal achievment of national economical development. As known generally, the government in Denpasar not only overcome the problem of urban farmer, but the problem of several beggars either. As these circumstances, it’s necessary to conduct an observation regarding a comparison between an amount of farmer’s  income and an amount of beggar’s income in Denpasar. The respondents in this resaearch divided by 30 farmers and 30 beggars, and samples are taken by accidental technic. In this comparison observation, the data of beggar’s income is one day. The goal of this reasearch is to identify the comparison between urban farmer’s income and beggars in Denpasar. The average income of farmers in 30 respondents in one day  obtained by farmers chili IDR 22.462, IDR 19.290 watermelon, rice IDR 19.167. While corn farmers suffered lossesf of IDR 4.483 in one day income derived from the land area 175 are average earnings of beggars in the city of Denpasar in one day IDR 63.833. Constraints farmers to farm in Denpasar is climate change causes changes in cropping patterns, the lack of availability of water for irrigation, and pest attack which can damage plant growth suggestions for solving the problem of farmers in Denpasar need assistance from the authorities. Problem handling the beggars can be evaluated from the condition in the area of origin. And conditions in the regions of origin of prevention is done so that they are not compelled to leave their villages and seek income in the city by away of beging.
Keywords: Farmers, earnings comparison, beggar